Efficacy and safety of acupuncture in post-stroke constipation: a systematic review and meta-analysis - Sun, Tianye; Wang, Kaiyue; Li, Lili; Yan, Mingyuan; Zou, Lin; Zhang, Mi; Yang, Songyi; Wu, Jing; Liu, Jinmin (Frontiers in Neuroscience, 2023)
Background and objective Post-stroke constipation (PSC) is a common complication of strokes that seriously affects the recovery and quality of life of patients, and effective treatments are needed. Acupuncture is a viable treatment option, but current evidence is insufficient to support its efficacy and safety. This study aims to evaluate the efficacy and safety of acupuncture in the treatment of PSC. Methods A systematic search of eight databases was conducted to identify PSC-related randomized clinical trials from the inception of each database through May 2023. Methodological quality assessment was conducted by RoB 2.0, meta-analysis was conducted by RevMan 5.3 and Stata 15.1, and evidence quality was evaluated by GRADE. Moreover, reporting quality of acupuncture interventions was assessed using the Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA). Results Thirty RCTs involving 2,220 patients were identified. We found that acupuncture was superior to conventional treatment (CT) in improving total responder rate [risk ratio (RR): 1.16, 95% confidence interval (CI): 1.09 to 1.25, p < 0.0001], decreasing constipation symptom scores [standardized mean difference (SMD): -0.65, 95% CI: −0.83 to −0.46, p < 0.00001], increasing serum P substance (SP) levels (SMD: 1.92, 95% CI: 0.47 to 3.36, p = 0.009), reducing the time to first bowel movement (BM) (SMD: -1.19, 95% CI: −2.13 to −0.25, p = 0.01), and lowing serum vasoactive intestinal peptide (VIP) levels (SMD: –2.11, 95% CI: −3.83 to −0.38, p = 0.02). Furthermore, acupuncture plus CT was superior regarding total responder rate (RR: 1.26, 95% CI: 1.17 to 1.35, p < 0.00001), serum SP levels (SMD: 2.00, 95% CI: 1.65–2.35, p < 0.00001), time to first BM (SMD: –2.08, 95% CI: −2.44 to −1.71, p < 0.00001), and serum VIP levels (SMD: –1.71, 95% CI: −2.24 to −1.18, p < 0.00001). However, regarding Bristol Stool Scale (BSS) score, acupuncture plus CT was superior to CT (SMD: -2.48, 95% CI: −3.22 to −1.73, p < 0.00001), while there was no statistically significant difference between acupuncture and CT (SMD: 0.28, 95% CI: −0.02 to 0.58, p = 0.07). Acupuncture causes fewer AEs than CT (RR: 0.13, 95% CI: 0.06 to 0.26, p < 0.00001), though there was no statistically significant difference between acupuncture plus CT vs. CT (RR: 1.30, 95% CI: 0.60 to 2.84, p = 0.51). Conclusion Acupuncture may be an effective and safe therapy for PSC. However, given the inferior quality of clinical data, additional well-designed RCTs are required to confirm these findings.